Foodborne disease: why it matters for food security, nutrition and climate change adaptation - Grace, Delia (International Livestock Research Institute, 2025)
Delia Grace, Professor on Food Systems at the Natural Resources Institute, shines a light on one of the most overlooked threats to nutrition and climate resilience: foodborne disease. Drawing on two decades of research, she presents practical, scalable solutions that have reduced contamination in informal markets while supporting livelihoods. Her “three-legged stool” approach, combining policy reform, low-cost technologies, and behavioral nudges, shows how food safety can be transformed from the ground up. With climate change intensifying food safety risks, her work offers a clear path to safer, more sustainable food systems.